Efficacy and Mechanisms of Antioxidant Compounds and Combinations Thereof against Cisplatin-Induced Hearing Loss in a Rat Model - Liliana Carles; Alejandro Gibaja; Verena Scheper; Juan C. Alvarado; Carlos Almodovar; Thomas Lenarz; José M. Juiz (MDPI AG, 2024)
Cisplatin is an election chemotherapeutic agent used for many cancer treatments. Its cytotoxicity against neoplastic cells is mirrored by that taking place in healthy cells and tissues, resulting in serious adverse events. A very frequent one is ototoxicity, causing hearing loss which may permanently affect quality of life after successful oncologic treatments. Exacerbated oxidative stress is a main cytotoxic mechanism of cisplatin, including ototoxicity. Previous reports have shown antioxidant protection against cisplatin ototoxicity, but there is a lack of comparative studies on the otoprotectant activity and mechanism of antioxidant formulations. Here, we show evidence that a cocktail of vitamins A, C, and E along with Mg++ (ACEMg), previously shown to protect against noise-induced hearing loss, reverses auditory threshold shifts, promotes outer hair cell survival, and attenuates oxidative stress in the cochlea after cisplatin treatment, thus protecting against extreme cisplatin ototoxicity in rats. The addition of 500 mg N-acetylcysteine (NAC), which, administered individually, also shows significant attenuation of cisplatin ototoxicity, to the ACEMg formulation results in functional degradation of ACEMg otoprotection. Mg++ administered alone, as MgSO4, also prevents cisplatin ototoxicity, but in combination with 500 mg NAC, otoprotection is also greatly degraded. Increasing the dose of NAC to 1000 mg also results in dramatic loss of otoprotection activity compared with 500 mg NAC. These findings support that single antioxidants or antioxidant combinations, particularly ACEMg in this experimental series, have significant otoprotection efficacy against cisplatin ototoxicity. However, an excess of combined antioxidants and/or elevated doses, above a yet-to-be-defined "antioxidation threshold", results in unrecoverable redox imbalance with loss of otoprotectant activity.